Pengaruh Inovasi Produk, Orientasi Pasar, dan Manajemen Risiko Terhadap Kinerja UMKM di Kabupaten Sumbawa - Yeni Yunisyah; Rian Hardiansyah (SENTRI: Jurnal Riset Ilmiah, 2026)
Micro, Small, and Medium Enterprises (MSMEs) hold strategic importance in Indonesia’s economy, contributing 60.5 percent to the national GDP and absorbing 97 percent of the workforce. Nonetheless, their labor productivity remains approximately one-third that of large enterprises, indicating a critical performance gap that necessitates empirical investigation of internal capability drivers, particularly in high-potential yet underperforming regions such as Sumbawa Regency. Prior studies have examined product innovation, market orientation, and risk management in isolation, with limited integration into a unified model. Furthermore, no research has contextually investigated these three variables simultaneously within Sumbawa Regency using a comprehensive multidimensional performance measure. This study offers a distinct contribution by integrating product innovation, market orientation, and risk management into a single unified MSME performance model grounded in the non-metropolitan context of Sumbawa Regency — a combination that has not been empirically tested in this specific regional setting. This study empirically examines the partial and simultaneous effects of product innovation, market orientation, and risk management on MSME performance in Sumbawa Regency. An explanatory quantitative approach was employed, utilizing a five-point Likert-scale questionnaire administered to 100 purposively sampled MSME operators. Data were analyzed through multiple linear regression using SPSS 26, following validity, reliability, classical assumption, and hypothesis testing. All hypotheses were supported: product innovation exerted the most dominant positive and significant effect on performance; market orientation demonstrated a significant positive effect; risk management positively and significantly influenced performance; and the three variables simultaneously produced a significant joint effect (R² = 53.7 percent). These findings imply that the integrated strengthening of product innovation capability, market orientation, and risk management constitutes the key strategic framework for enhancing MSME performance in non-metropolitan regions. Local government is recommended to design evidence-based policy interventions anchored in these three capability pillars, leveraging Sumbawa’s rich cultural heritage as a natural source of product differentiation and competitive advantage.